MEMBANGUN KARAKTER ENTREPRENEURSHIP DALAM MEWUJUDKAN SUMBER DAYA MANUSIA YANG MANDIRI, KREATIF, INOVATIF DAN BERDAYA SAING - Titin Dunggio; Pikran Harun; Gitariya Yahya (Journal of Hulonthalo Service Society (JHSS), 2022)
In the current era of globalization, the development of quality human resources (HR) is the key to achieving progress and competitiveness of a country. One effective approach to improving the quality of human resources is through the development of entrepreneurial character. This character includes independent, creative, innovative, and competitive traits. The purpose of this activity is to build entrepreneurial character in realizing independent, creative, innovative and competitive human resources in Toto Utara Kabila Village. The implementation method is carried out in two stages, namely the planning and debriefing stage and the second stage of activity implementation. The results of the activity were attended by 30 participants, the head of North Toto village and the activity went smoothly and well. With this activity the community knows the importance of independent, creative, innovative and competitive entrepreneurship characters.